Pengaruh Iklim Organisasi dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Dinas Energi dan Sumber Daya Mineral Provinsi Kalimantan Timur (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of organizational climate and work motivation on employee performance at the Energy and Mineral Resources Office of East Kalimantan Province. The research is based on the strategic role of public employees in the energy sector to support regional policy implementation and the importance of creating a productive and motivated work environment. A quantitative approach was used through a survey method by distributing questionnaires to 68 employees. Data were analyzed using multiple linear regression with SPSS version 25. The results show that both organizational climate and work motivation have a positive and significant influence on employee performance, both partially and simultaneously. The coefficient of determination (R²) of 0.329 indicates that 32.9% of the variation in employee performance can be explained by the two variables. These findings highlight the importance of establishing a conducive organizational climate and enhancing employee motivation to support optimal performance in the public sector.